Kajian Hukum Netralitas ASN dalam Konteks Pemilu dan Pilkada 2024 di Provinsi Bali - Pratiwi, Ida Ayu Windhari Kusuma; Yadnya, Putu Andhika Kusuma; Dharma, Ida Bagus Wirya (Bali Membangun Bali: Jurnal Bappeda Litbang, 2024)
Purpose: This study aims to examine the regulations and legal consequences of civil servant (ASN/aparatur sipil negara) neutrality in the context of the 2024 General Elections and Regional Elections in Bali Province, and to provide practical recommendations to assist civil servants in maintaining neutrality. Research methods: A normative legal method with a statutory regulation approach using concept and case analysis is applied in this study. In this case, primary and secondary data are utilized through bibliography and description techniques. Results and discussion: The regulations regarding civil servant neutrality are quite comprehensive, yet there are still significant violations which result in disciplinary and criminal sanctions for civil servants in Bali who are proven to be non-neutral. Implication: This study highlights the importance of strengthening socialization, monitoring, and enforcement of rules to ensure that civil servants understand and adhere to neutrality provisions in performing their duties, while also considering the social and cultural factors that influence the community in Bali.